Critical Role of Lipid Composition in Membrane Permeabilization by Rabbit Neutrophil Defensins - Kalina Hristova; Michael E. Selsted; Stephen H. White (1997)
We have examined the interactions of the six known rabbit neutrophil defensin antimicrobial peptides with large unilamellar vesicles (LUV) made from various lipid mixtures based on the lipid composition of Escherichia coli membranes. We find that the permeabilization of LUV made from E. coliwhole lipid extracts differs dramatically from that of single-component LUV made from palmitoyl-oleoyl-phosphatidylglycerol (POPG). Specifically, defensins NP-1, NP-2, NP-3A, NP-3B, and a natural mixture of the six defensins cause fast nonpreferential leakage of high molecular weight dextrans as well as the low molecular weight fluorophore/quencher pair 8-aminonapthalene-1,3,6 trisulfonic acid (ANTS)/p-xylene-bis-pyridinium bromide (DPX) from E. coli whole lipid LUV through large, transient membrane lesions. In contrast, release of ANTS/DPX from POPG LUV induced by the defensins is slow and graded with preference for DPX (Hristova, K., Selsted, M. E., and White, S. H. (1996) Biochemistry35, 11888–11894). Interestingly, defensins NP-4 and NP-5 alone do not induce leakage from E. coli whole lipid LUV, whereas only NP-4 is ineffective with POPG LUV. Examination of the sequences of the six defensins suggests that the inactivity of NP-4 and NP-5 may be due to their lower net positive charge and/or the substitution of a Thr for the Arg or Lys that follows the fourth Cys residue. We found the presence of three major lipid components of E. coli whole lipid to be essential for creation of the large lesions observed in LUV: phosphatidylethanolamine, phosphatidylglycerol, and cardiolipin. Cardiolipin appears to play a key role because no leakage can be induced when only phosphatidylglycerol and phosphatidylethanolamine are present. These results indicate the importance of membrane lipid composition in the permeabilization of cell membranes by rabbit defensins.